2014
DOI: 10.4236/aar.2014.34040
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Thinking Underlying People with Diabetes’ Beliefs on Health Outcomes: An Information Integration Theory Approach

Abstract: A sample of 76 older adults (27 with diabetes and 49 without diabetes) were selected to judge three information factors, metamemory related to-drug organization-stress and physical activity in relation to their perception of self-care. In order to do so, an Integration Information Theory was considered to determine systematic cognitive algebra rules underlying judgment about 24 different health self-care scenarios. Results indicate that older adults without diabetes use a summative cognitive rule to integrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…A las actividades de cuidado que le brindan mayor importancia son los medicamentos y cuidado de los pies, similar a lo mencionado en el artículo de Hernández-Cortés et al, (14) donde menciona que los adultos mayores le dan mayor peso a la medicación que otros factores de cuidado a la salud.…”
Section: Discussionunclassified
“…A las actividades de cuidado que le brindan mayor importancia son los medicamentos y cuidado de los pies, similar a lo mencionado en el artículo de Hernández-Cortés et al, (14) donde menciona que los adultos mayores le dan mayor peso a la medicación que otros factores de cuidado a la salud.…”
Section: Discussionunclassified
“…Individuals impose consciously or unconsciously systematic thinking on every day health behavior [1] [2]. These health cognitions (thoughts and feelings) de- …”
Section: Introductionmentioning
confidence: 99%
“…In turn, this lack of cognitive specification limits prediction power of adherence to healthy behavior. For instance, Hernandez et al [2] have shown that cognitive specification of systematic thinking underlying judgment formation toward health risk behaviors in people with diabetes allows specific intervention on medication schedules and dietary behavior. Specifically, these authors found that diabetics tend to use a weighted summative cognitive rule to integrate sources of information on medication schedules, stress factors and exercise.…”
mentioning
confidence: 99%